Analysis of Implementation of Margins with Flat Installments in Murabahah Financing on Products iB PMG Motor Vehicles in the Bank of Sumut Sharia KCP HM Yamin - Susi Kinanti; Yenni Samri Juliati Nasution; Mawaddah Irham (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aims to determine the mechanism for implementing margins with flat installments in murabahah contracts and the factors that influence them on motor vehicles ib PMG products at Bank Sumut Syariah KCP HM Yamin. This study uses a descriptive qualitative approach with primary and secondary data sources. This study used data collection techniques by interviewing. The results of the research are that the mechanism for implementing margins on flat installments on murabahah contracts for iB PMG Motorized Vehicle products at Bank Sumut Syariah begins with the analysis of the treasure division by considering various costs and all that affect the financial value of Bank Sumut Syariah which is then discussed together with the DPS of the Bank. Sumut Syariah will then be presented at a joint meeting with Bank Sumut Syariah officials to agree on the provisions that have been analyzed and proposed by the treasure division. The size of Bank Sumut Syariah's margin is influenced by cost factors related to Overhead Costs, Profit Sharing of Third Party Funds (DPK), and Volume of Murabahah Financing. This study aims to determine the mechanism for implementing margins with flat installments in murabahah contracts and the factors that influence them on motor vehicles ib PMG products at Bank Sumut Syariah KCP HM Yamin. This study uses a descriptive qualitative approach with primary and secondary data sources. This study used data collection techniques by interviewing.